2016
DOI: 10.1523/jneurosci.0156-16.2016
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Structure of Neural Variability in the Cortical Representation of Speech Sounds

Abstract: Accurate sensory discrimination is commonly believed to require precise representations in the nervous system; however, neural stimulus responses can be highly variable, even to identical stimuli. Recent studies suggest that cortical response variability decreases during stimulus processing, but the implications of such effects on stimulus discrimination are unclear. To address this, we examined electrocorticographic cortical field potential recordings from the human nonprimary auditory cortex (superior tempor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…An abundance of work has aimed to assess whether observed correlated variability is beneficial or detrimental for neural coding[6, 912, 16, 19, 2433]. These studies often quantify the discriminability or fidelity of a neural code with the linear Fisher information (LFI, see Section) [36], which is a measure of how well the neural activity could be used to discriminate between different stimuli.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…An abundance of work has aimed to assess whether observed correlated variability is beneficial or detrimental for neural coding[6, 912, 16, 19, 2433]. These studies often quantify the discriminability or fidelity of a neural code with the linear Fisher information (LFI, see Section) [36], which is a measure of how well the neural activity could be used to discriminate between different stimuli.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have found pairwise correlations in the trial-to-trial variability of the firing rates of simultaneously recorded neurons, often called correlated variability or noise correlations [39]. The correlated variability observed in experimental studies typically depends on the tuning and stimuli [1012].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We take advantage of tools provided in the nipy software package ( https://github.com/nipy/nipy/ ), dural surface reconstruction from ielu (LaPlante et al, 2016 ), 3D plotting in mayavi ( http://mayavi.sourceforge.net/ ; Ramachandran, 2001 ), and extend on functions available in the MATLAB-based CTMR package (Hermes et al, 2010 ). This protocol has been used to localize and label electrodes in our previously published work (Dichter et al, 2016 ; Hamilton et al, 2016 ; Leonard et al, 2016 ; Moses et al, 2016 ; Muller et al, 2016b ; Tang et al, 2017 ). In an effort to promote open and affordable access to these tools, all requirements to run the pipeline (aside from physical hardware) are freely available for download at no cost to the user.…”
Section: Introductionmentioning
confidence: 99%
“…How these perceptual and articulatory distinctions are reflected in cortex is a question of significant theoretical and translational interest. Prior studies have used intracranial high-density electrode arrays, or electrocorticography (ECoG), to measure cortical activity during speech listening (Dichter et al, 2016;Mesgarani et al, 2014;Chang et al, 2010; see Leonard and Chang, 2014 for a review). Mesgarani et al (2014) showed that different electrode sites across superior temporal gyrus responded to different subsets of phonemes in a manner consistent with their articulatory properties (particularly their manner of articulation).…”
Section: Introductionmentioning
confidence: 99%